2009
DOI: 10.1080/10508410903187547
|View full text |Cite
|
Sign up to set email alerts
|

Mental Workload in Aircraft and Simulator During Basic Civil Aviation Training

Abstract: This study investigated mental workload in basic civil aviation training. Heart rate, eye movement, and subjective ratings from 11 students were collected during simulator and aircraft sessions. Results show high correspondence in psychophysiological reactions between the sessions. For some flight segments, heart rate was consistently lower in the simulator, suggesting higher mental workload in the aircraft. Differences in heart rate during rejected takeoff and engine failure indicate that the increase of work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 19 publications
2
32
0
1
Order By: Relevance
“…Relevant studies showed that both heart rate and heart rate variability (HRV) indexes can effectively reflect the different levels of mental workload. [15][16][17] However, there was some limitation for using frequency-domain index of HRV to reflect the physiological change, because it is affected by the length of data extraction period, and the essence of physiological change reflected still needs further study. 18 Besides, relevant studies also indicated that within a certain period of time (5 min), there is a significant correlation between time-domain related indexes and frequency-domain related indexes in R-R interval.…”
Section: Ecg Data Recordingmentioning
confidence: 99%
“…Relevant studies showed that both heart rate and heart rate variability (HRV) indexes can effectively reflect the different levels of mental workload. [15][16][17] However, there was some limitation for using frequency-domain index of HRV to reflect the physiological change, because it is affected by the length of data extraction period, and the essence of physiological change reflected still needs further study. 18 Besides, relevant studies also indicated that within a certain period of time (5 min), there is a significant correlation between time-domain related indexes and frequency-domain related indexes in R-R interval.…”
Section: Ecg Data Recordingmentioning
confidence: 99%
“…The evolution of simulation in aviation has mainly been technology-driven, from the introduction of visual systems and computer graphics (Dennis andHarris 1998, Lee 2005), to recent additions of satellite imagery to represent the visual scene of the ground below and current moves to further integrate into simulations the role of air traffic control (Longridge et al 2001). Although this increase of face-validity to improve training quality has been questioned (Roscoe 1991, Salas et al 1998, Dahlstro¨m and Na¨hlinder 2007, there seems to be a taken for granted assumption within the aviation community that incremental quantitative progress (e.g. more computing power, higher resolution, greater visual angles) adds up to a positive qualitative difference.…”
Section: Simulation Fidelity and Development Of Resiliencementioning
confidence: 99%
“…However, over time the continually increased demand for higher levels of fidelity to make simulations look 'real' increase cost and lower availability of training simulators (one has to keep in mind the huge capital investment a commitment to this style of simulation requires). Even though there have been few studies of transfer of training from photorealistic simulators to aircraft (Carretta andDunlap 1998, Dahlstro¨m andNa¨hlinder 2007) and the problems of performing such studies have been documented (Hays et al 1992, Bell andWaag 1998), the assumed relation between fidelity and transfer of training seems to prevail in the aviation industry (in other industries too, e.g. maritime transport, nuclear power, medicine, as well as in the military).…”
Section: Simulation Fidelity and Development Of Resiliencementioning
confidence: 99%
“…Nowadays, on the contrary, an eye tracker system can be easily embedded in a flight simulator or even a real aircraft. Thus, eye-tracking has already been successfully used to conduct high-fidelity flight simulator experiments [26][27][28] and real flight experiments [29,30].…”
Section: Introductionmentioning
confidence: 99%